Monetary Policy in Sub-Saharan Africa - Berg, Andrew (International Monetary Fund, 2018)
Monetary policy in sub-Sahara Africa (SSA) has undergone an important transformation in recent decades. With the advent of sustained growth and generally stable fiscal policies in much of the region, many countries are now working to modernize their monetary policy frameworks. This book provides a comprehensive view of the many monetary policy issues in sub-Saharan Africa. It reflects an effort to fill a gap in the current literature and collects research by staff of the IMF and other institutions, as well as from policymakers within central banks in SSA. The chapters explore the many dimensions of monetary policy in SSA. This volume will serve as an important reference for academics and policymakers and will inform future policy debates. The book highlights two points, one policy-related and the other methodological. Although these countries differ in important ways from advanced and emerging market countries, the monetary policy issues they face are not fundamentally different from those faced elsewhere. Policy aims to provide an anchor for inflation over the medium term while also responding to external and domestic shocks. Likewise, Sub-Saharan African countries are in the process of modernizing their policy frameworks, by clarifying their objectives and improving their operational frameworks, making policy increasingly forward-looking and improving their forecasting and analytical capacity.